NILAI PENDIDIKAN RELIGIUS, TOLERANSI DAN GEMAR MEMBACA DALAM NOVEL AYAT-AYAT CINTA 2 - Gusti Alamsyah Afandi (Tarbiya Islamica, 2016)
This study aims to determine the value of religious character education, tolerance, and love of reading in the novel Ayat-ayat Cinta 2 by Habiburrahman El Shirazy. Describing quotation data regarding religious character values, tolerance character values, and reading character values in the novel Ayat-ayat Cinta 2 by Habiburrahman El-Shirazy. Then analyzed and discussed in this study. This research uses a qualitative approach and the type of library research. The data technique uses documentation techniques. The data analysis technique used is content analysis. The results showed that: 1) The value of character education in the novel Ayat-ayat Cinta 2 by Habiburrahman El Shirazy regarding the value of religious character found 68 quotes divided into 10 categories, 5 quotes for tolerance character, and 8 quotes for characters who like reading. 2) The value of tolerance character education 5 quotes divided into 3 categories. 3) The reading character value is 8 quotes with 4 categories.